MEASURING THE SIGNIFICANCE OF DEEP LEARNING IMPLEMENTATION AND TEACHER PROFESSIONALISM IN BOOSTING THE QUALITY OF STUDENT LEARNING OUTCOMES - Latifah Latifah; Ima Widiyanah; Ainur Rifqi (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
The quality of education is highly dependent on the professionalism of teachers as the spearhead of the learning process. However, reality shows that student learning outcomes are still suboptimal, partly due to weak professional competence and teachers' low ability to design and implement adaptive learning. This study aims to analyze the significance of the application of deep learning and teacher professionalism in improving the quality of student learning outcomes through a comprehensive review of various previous studies. The type of research used is qualitative research with a library research method. Data sources come from scientific journals, academic books, proceedings, and credible documents published between 2019 and 2024. Data were collected through documentation techniques and analyzed using a qualitative descriptive approach through the stages of reduction, presentation, and drawing conclusions. The results show that teacher professionalism contributes significantly to improving student learning outcomes through mastery of pedagogical, professional, social, and personality competencies. Professional teachers are able to create a productive learning environment, implement innovative learning strategies, and foster student learning motivation. In addition, factors such as ongoing training, principal support, teaching experience, and intrinsic motivation also strengthen teacher professionalism. deep learning has also been shown to improve conceptual understanding, intrinsic motivation, and student engagement. This study confirms that improving teacher professionalism and implementing deep learning are strategic prerequisites for strengthening the quality of 21st-century education. Keywords: deep learning; learning outcomes; teacher professionalism; quality of education Abstrak Mutu pendidikan sangat bergantung pada kualitas profesionalisme guru sebagai ujung tombak dalam proses pembelajaran. Namun, realitas menunjukkan bahwa capaian hasil belajar siswa masih belum optimal, antara lain disebabkan oleh lemahnya kompetensi profesional dan rendahnya kemampuan guru dalam merancang serta melaksanakan pembelajaran yang adaptif. Penelitian ini bertujuan untuk menganalisis signifikansi penerapan pembelajaran mendalam dan profesionalisme guru dalam meningkatkan mutu hasil belajar murid melalui kajian komprehensif terhadap berbagai penelitian terdahulu. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan metode studi pustaka (library research). Sumber data berasal dari jurnal ilmiah, buku akademik, prosiding, dan dokumen kredibel yang diterbitkan antara tahun 2019–2024. Data dikumpulkan melalui teknik dokumentasi dan dianalisis menggunakan pendekatan deskriptif kualitatif melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa profesionalisme guru berkontribusi signifikan terhadap peningkatan hasil belajar siswa melalui penguasaan kompetensi pedagogik, profesional, sosial, dan kepribadian. Guru profesional mampu menciptakan lingkungan belajar yang produktif, menerapkan strategi pembelajaran inovatif, serta menumbuhkan motivasi belajar siswa. Selain itu, faktor seperti pelatihan berkelanjutan, dukungan kepala sekolah, pengalaman mengajar, dan motivasi intrinsik turut memperkuat profesionalisme guru. Pembelajaran mendalam juga terbukti meningkatkan pemahaman konseptual, motivasi intrinsik, serta keterlibatan siswa. Penelitian ini menegaskan bahwa peningkatan profesionalisme guru dan implementasi pembelajaran mendalam merupakan prasyarat strategis untuk memperkuat mutu pendidikan abad ke-21. Kata Kunci: hasil belajar, pembelajaran mendalam, profesionalisme guru, mutu pendidikan